Strategi Komunikasi Kader Pemberdayaan Masyarakat dalam Menangani Stunting di Desa Sindang Pakuon Sumedang - Nurlimah, Nila; Utaridah, Nanda; Yani, Indri (Jurnal Ilmu Komunikasi, 2025)
Stunting is a serious challenge to national development because it affects the quality of human resources in the future. Sumedang Regency, West Java, is known to have successfully reduced the prevalence of stunting through the Accelerated Stunting Reduction (PPS) program, which is integrated with the e-SIMPATI application. This study aims to describe the communication strategies of posyandu cadres in supporting program implementation in Sindangpakuon Village, Cimanggung District. The research method used a qualitative approach with a constructivist paradigm through in-depth interviews and participatory observation. The results showed that the communication strategies of cadres were carried out through cross-actor collaboration, interpersonal approaches, the use of digital media, and continuous evaluation using the RACE (Research, Action, Communication, Evaluation) model. Additionally, it was found that limiting factors included digital literacy constraints and uneven levels of community participation; however, cadres were able to overcome these challenges through local innovations. These findings emphasize the importance of adaptive and participatory communication strategies in bridging government policies with the social conditions of rural communities.